Molecular phylogeny of Panicum s. Str. (Poaceae, Panicoideae, Paniceae)and insights into its biogeography and evolution - Zuloaga, Fernando Omar (2018)
Panicum sensu stricto is a genus of grasses (Poaceae) with nearly, according to this study, 163 species distributed worldwide. This genus is included in the subtribe Panicinae together with Louisiella, the latter with 2 species. Panicum and subtribe Panicinae are characterized by including annual or perennial taxa with open and lax panicles, and spikelets with the lower glume reduced; all taxa also share a basic chromosome number of x = 9 and a Kranz leaf blade anatomy typical of the NAD-me subtype photosynthetic pathway. Nevertheless, the phylogenetic placements of many Panicum species, and the circumscription of the genus, remained untested. Therefore, phylogenetic analyses were conducted using sequence data from the ndhF plastid region, in an extensive worldwide sampling of Panicum and related genera, in order to infer evolutionary relationships and to provide a phylogenetic framework to review the classification of the genus. Diversification times, historical biogeography and evolutionary patterns of the life history (annual vs. perennial) in the subtribe and Panicum were also studied. Results obtained provide strong support for a monophyletic Panicum including 71 species and 7 sections, of which sections Arthragrostis and Yakirra are new in the genus; 7 new combinations are made here. Furthermore, 32 species traditionally assigned to Panicum were excluded from the genus, and discussed in other subtribes of Paniceae. Our study suggested that early diversification in subtribe Panicinae and Panicum occurred through the Early-Mid Miocene in the Neotropics, while the subsequent diversification of its sections mainly occurred in the Late Miocene-Pleistocene, involving multiple dispersals to all continents. Our analyses also showed that transition rates and changes between annual and perennial life history in Panicum were quite frequent, suggesting considerable lability of this trait. Changes of the life history, together with C4 photosynthesis, and the multiple dispersal events since the Mid Miocene, seem to have facilitated a widespread distribution of the genus. All these findings contribute to a better understanding of the systematics and evolution of Panicum.